Individuação e expatriação: resiliência da esposa acompanhante - Borba, Daniela (2008)
The present study has intended to understand the acculturation experience in Brazil, among ten Latin-American Spanish speaking women, following their executive expatriate husbands. Expatriation is a form of globalized immigration, characterized by a change of countries without the changing companies. The verbal material from the interviews (were treated under the Collective Subject, Speech Method), the resilience test content, as well as the dialogue between three approaches: intercultural psychology, human resilience and the analytical psychology of C. G. Jung, have contributed to establishing findings that can contribute with the understanding of a transformation process that takes place in this context. A initial period of mourning is started by the enrooting process and the ambivalent losses from: social net and gender roles changing, professional versus family conflict and, cultural and intrapsychic boundaries destabilization. Such adversity has induced, through self overcoming, the development in other areas such as: the recognition of deep relationships importance, flexibility, patience, positive attitude, new cultural codes acquisition, deepening of family relations, and the increase of motherhood and femininity. On the other hand, some risk factors for this experience have been found. Their relationship with the Brazilian culture, for instance, were characterized as superficial e restrict, for the majority, indicating a acculturation process as separation. This defensive form of intercultural relation, allowed the participants to perceive some Brazilian inferior cultural complex symptoms (low self-esteem, passiveness, uncommitted behavior, pleasure search and law disrespect). Shallowness, thus, occurs both ways of this intercultural encounter. Risk factors were also found: a high control of impulses joined to a low regulation of emotions indicates that, as repression tends to increase, the emotional control diminish, stopping wishes and plans from happening, and also expanding the dependence on the spouse. Therefore, to stimulate a healthy development is most important that health and organizational professionals, and the participants themselves, notice and encourage: 1. acculturation by means of cultural integration, 2. the balance of resilience factors, and 3. the individuation process resulting from the elaboration of deeper layers of the unconscious, brought up by the intercultural experience. As conclusion, the path of development for these women indicates the need of investments in their own projects, apart from family, so that, through self-accomplishment, they turn expatriation into their own journey